Ethical Product Sourcing in the Starbucks Coffee Supply Chain - Munson, Chuck (Charles Lee); Smith, Dustin M., 1975- (Pearson, 2013)
This case study focuses on Starbucks' challenges in integrating Fair Trade coffee into its global supply chain, empowering family farmers and workers to escape poverty. With its large market presence, Starbucks has been under pressure to increase Fair Trade imports. However, Fair Trade coffee is, by design, more expensive than similar goods. How has Starbucks approached Fair Trade? What is the real value and limitations of the Fair Trade model? What obstacles does Starbucks face in making Fair Trade work for everyone, including customers? Focusing on realistic issues and challenges, this case study offers exceptional value to both students and practitioners. Author: Dustin Smith, Washington State University.